Pseudopapilloedema in the linear naevus syndrome. - Campbell, S. H. (1992)
This case report describes the ophthalmic findings in a child with the linear naevus syndrome. The patient was referred by the Department of Paediatric Neurology with 'unilateral papilloedema'. This was thought to be a form of pseudopapilloedema, a finding that has not been previously described in this syndrome.